2022
DOI: 10.1136/bmjopen-2022-062975
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the COVID-19 pandemic on maternal and perinatal health service utilisation and outcomes in Mozambique: an interrupted time series analysis

Abstract: ObjectivesTo measure the effects of the COVID-19 pandemic on maternal and perinatal health services and outcomes in Mozambique.DesignThis is an observational study analysing routine service delivery data using interrupted time series analysis. We used 43 months of district-level panel data with April 2020 as the point of interruption, adjusting for seasonality and population growth to analyse service utilisation outcomes.SettingThe 222 public health facilities in Nampula Province, Mozambique, from January 2018… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 29 publications
0
9
0
Order By: Relevance
“…A study in Nampula Province, Mozambique noted no disruptions and an actual increase in ANC visits, comparing data 2 years before COVID lockdowns to July 2021 (Lydon et al, 2022). Telehealth and mobilisation of community health workers were important interventions that improved education and outreach for COVID-19 across geographically diverse regions of Bangladesh, but they were not optimised to ensure the continuity of essential health and nutrition services (Gaitán-Rossi et al, 2022).…”
Section: Themementioning
confidence: 99%
“…A study in Nampula Province, Mozambique noted no disruptions and an actual increase in ANC visits, comparing data 2 years before COVID lockdowns to July 2021 (Lydon et al, 2022). Telehealth and mobilisation of community health workers were important interventions that improved education and outreach for COVID-19 across geographically diverse regions of Bangladesh, but they were not optimised to ensure the continuity of essential health and nutrition services (Gaitán-Rossi et al, 2022).…”
Section: Themementioning
confidence: 99%
“…Included studies showed mixed results concerning institutional deliveries that comprise normal vaginal deliveries and caesarean sections. Even though eight studies highlighted a reduction in the number/proportion of institutional deliveries ( 36 , 49–51 , 56 , 61 , 62 , 67 , 71 ), six reports ( 38 , 43 , 63 , 73–75 ) observed growth and two studies ( 34 , 42 ) did not find any changes with respect to this indicator. The results varied depending on the setting in three multi-centred studies ( 64 , 77 , 78 ), making it difficult to provide a generalised conclusion.…”
Section: Resultsmentioning
confidence: 92%
“…Albeit no changes were made to the standard antenatal care protocol in the majority of settings, increased interruptions in antenatal care ( 76 ) and a decrease in antenatal care coverage ( 42 ), antenatal recruitment rate and prenatal visit completion rate ( 59 ), antenatal care registrations ( 62 ), number/proportion of antenatal care visits ( 34 , 36–38 , 47 , 49 , 56 , 58 , 61 , 65 , 67 , 71 , 72 , 74 , 75 ) and attendance ( 50 , 51 , 70 , 77 , 78 ) was noticed in most cases as compared to the pre-pandemic period. However, Pillay and colleagues ( 73 ) observed no difference in the number of first antenatal care visits in South Africa and Lydon and colleagues ( 43 ) detected an increased number of first antenatal visits and no difference in the number of fourth antenatal visits in Mozambique. No difficulties in accessing antenatal care were declared in one study originated from India ( 63 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations